Appraisal of Selected Heavy Metals and Potential Health Risk in Commercial Tea Sold in South Western, Nigeria - Aikpokpodion , Paul E.; Raphael, Oyeniran (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Tea is the most popular beverage all over the world and second to water. In recent decades, there has been an extensive increase in the level of heavy metal contamination in tea. The study aimed at evaluating the level of Cu, Co, Cr, Cd, Pb and Ni in some commercial green and black tea sold within Ibadan, Nigeria. Seven of the popular tea brands (Halmak green tea, Strong black tea, Lipton, Herb tea, Top tea, City tea and Kirkland green tea) among consumers were purchased in the open market. Heavy metals were quantified with Atomic Absorption spectrophotometer. Total Cu ranged between 11.02 and 24.12mgkg-1 while total Cr and Ni were within the range of 5.50-23.00 and 3.50-8.00 mgkg-1 respectively. After infusion of tea samples, 40.00, 37.73 and 16.25% of total Cu in Halmak (HM) green tea, Stong black tea (ST) and Lipton (LP) black tea was leached into tea drink respectively while 69.23, 16.22 and 15.20 % of total Ni in HM green tea, STG black tea and LP black tea was leached into tea drink respectively. The values of estimated daily intake and target hazard quotient obtained for the investigated commercial tea were within safe limit. Hence, regular consumers of the products are not likely to suffer health threat from metal contamination.